TREATMENT AND EVALUATION OF QUALITY VALUATION PROCESSOF CONSTRUCTIONAL PROJBCTS - Entisar K. Algeelawee (Journal of Engineering, 2024)
The importance of the study of the quality concepts and its management ancl the control on it ,has been increased and became one of the important subjects in the study and researches since the success of any consffuction projects is limited through the control on the important axel of the projects which are quality ,cost and time . From this the idea of the research subject cane . In concentrating on many factors which are influent on the quahty of the works ,in the construction projects and its management weather the effect was negative or positive that is reach suggestion of practical frame to valuate these effects on this quality evaluation process .